Pengaruh penilaian prestasi kerja, komitmen organisasi dan disiplin kerja terhadap kinerja karyawan pada pt. pelabuhan indonesia iv cabang samarinda - Ibnu Yarham Yamanie; Syaharuddin Y (JURNAL MANAJEMEN, 2016)
The purpose of this study is to uncover the effect of perfomance evalution, organizational commitment, and work discipline to staff performance porting branch Indonesia IV Samarinda, All 51 Staff were evaluated, and the result analyzed by linear regression using SPSS 16 for windows, Result showed that performance evalution, organizational commitment, and work discipline have positive effect to staff performance, Suggestion to future research is the researcher have to improve research quality and added or extended sample framerwork.Keyword: Job Achievement Estimation, organizational commitment, labor discipline, Performance Employee